Peningkatan Kualitas Generasi Sadar Kesehatan Reproduksi pada Mahasiswa Universitas Alifah Padang - Afzahul Rahmi; Nurul Prihastita Rizyana (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
Reproductive health according to the Government Regulation of the Republic of Indonesia Number 61 of 2014 is a state of complete physical, mental, and social health, not merely free from disease or disability related to the reproductive system, function, and process. Limited access to information on reproductive health results in a lack of knowledge, traits and risky behavior in adolescents which has an impact on the reproductive health status of adolescents. This situation requires the availability of adolescent-friendly health services that can meet the health needs of adolescents, especially reproductive health services that are friendly to adolescents. The purpose of this activity is to improve the quality of the reproductive health-conscious generation. Increasing the knowledge and skills of Alifah University students actively and independently in maintaining reproductive health and becoming a generation that is aware of reproductive health. The implementation of community service was carried out on December 16-17, 2024 through lectures, discussions and distribution of leaflets. Based on these problems, an increase in the generation's understanding of the importance of reproductive health was carried out. Evaluation was carried out with a pre-test and post-test. The findings indicate a significant improvement in participants’ knowledge, increasing from 78% prior to the intervention to 90% following the intervention.